The future of immortality remaking life and death in contemporary Russia - Bernstein, Anya (New Jersey : Princeton Univers. Press, 2019)
As long as we have known death, we have dreamed of life without end. In The Future of Immortality, Anya Bernstein explores the contemporary Russian communities of visionaries and utopians who are pressing at the very limits of the human. The Future of Immortality profiles a diverse cast of characters, from the owners of a small cryonics outfit to scientists inaugurating the field of biogerontology, from grassroots neurotech enthusiasts to believers in the Cosmist ideas of the Russian Orthodox thinker Nikolai Fedorov. Bernstein puts their debates and polemics in the context of a long history of immortalist thought in Russia, with global implications that reach to Silicon Valley and beyond. If aging is a curable disease, do we have a moral obligation to end the suffering it causes? Could immortality be the foundation of a truly liberated utopian society extending beyond the confines of the earth--something that Russians, historically, have pondered more than most? If life without end requires radical genetic modification or separating consciousness from our biological selves, how does that affect what it means to be human? As vividly written as any novel, The Future of Immortality is a fascinating account of techno-scientific and religious futurism - and the ways in which it hopes to transform our very being
Keywords: Russland; Gerontologie; Lebensverlängerung; Unsterblichkeit; Utopie